Development of a Mixed Reality Environment for the Rehabilitation of People with Impaired Mobility Using Gait Support Strategies - Machado, Fabiana Santos Vieira (2024)
Mobility significantly impacts quality of life, yet various health conditions can hinder it. These challenges are not limited to disease or injury-related impairments but also extend to age-related physical, cognitive, and sensory function losses. Smart Walkers and rehabilitation robotics offer solutions to improve functional capabilities and tailor therapy to individual needs, and in conjunction with Mixed Reality (MR), can also enhance motivation. This Doctoral Thesis aims to integrate advanced human-robot interfaces withMixed Reality to develop effective rehabilitation strategies. The UFES vWalker, a novel robotic assistance device introduced in this thesis, utilizes sensor interfaces to translate users' movement intentions into safe navigation. Integrated into an MR system, it combines virtual and physical environments and sensors, offering multimodal sensory feedback and enhanced human-robotenvironment interaction. The initial experiment with the MR system integrated haptic and visual feedback. Haptic feedback simulated an impedance tunnel to aid movement along the path, while visual feedback displayed the path in the virtual environment. Users with visual feedback completed tasks faster than those with only haptic feedback. The following experiment introduced a multimodal feedback system to assist visually impaired individuals in navigation. It included two main feedback systems: audio cues to guide users and vibration alerts for virtual obstacles. To prevent volunteers from viewing the virtual environment, visual feedback from the Oculus Quest headset, was disabled, creating a virtual blindfold. Three control strategies were used, each one designed for people with different residual mobility and cognitive capabilities. The strategies that offer more and less autonomy were more successful among volunteers, and exhibited similar mental, and physical demand. In the last experiment, a virtual obstacle avoidance strategy was introduced, utilizing a virtual laser sensor. This approach allowed users to move freely until an obstacle was detected, upon which the controller assists in navigating around it. Moreover, an interface was created to offer visual feedback on the key elements of the developed strategy. The volunteers found the MR system enjoyable, realistic, and encountered minimal confusion or difficulty during the experiment. Also, volunteers who received no introductory explanation about the interface were mostly able to infer their purpose. Therefore, it is clear that MR systems can provide considerable benefits to users who use rehabilitation assistance devices.